Aligning Of Carbon Nanotubes With An External Electric Field To Improve Thermal Conductivity Of Polydimethylsiloxane Nanocomposites Interface Material - Masraff, Mimi Syahira (Universiti Sains Malaysia, 2018)
Advancements in the semiconductor industry have lead to the miniaturization of components and increased power densities, resulting in thermal management issues. In response to this shift, finding multifunctional materials with excellent thermal conductivity and tailored electrical properties are becoming increasingly important. For this research thesis, the effect of an external electric field on aligning of carbon nanotubes was studied to develop and characterize thermally conductive polymer composites. A CNT/PDMS composite was prepared and an external electric field at various degrees was introduced during the curing to promote the carbon nanotubes alignment. The possibility of improving the thermal conductivity by introducing and aligning polymer fibers in the composites was investigated. The composites were characterized with respect to their physical, thermal, and electrical properties to propose possibilities of application in the electronic packaging industries. Experimental results reveal that the resulting nanocomposites exhibit anisotropic properties with significantly improved electrical and thermal conductivities in the alignment direction.